Up a country lane cookbook - Birkby, Evelyn (Bur oak original., 1993)
What can Evelyn Birkby possibly do to follow up the success of Neighboring on the Air: Cooking with the KMA Radio Homemakers? She can do what she has done in writing Up a Country Lane Cookbook. For forty-three years she has written a column entitled "Up a Country Lane" for the Shenandoah Evening Sentinel. Now she has chosen the best recipes from her column and interspersed them with a wealth of stories of rural life in the 1940s and 1950s, supplemented by a generous offering of vintage photographs. She has created a book that encompasses lost time. With chapters on "The Garden, & q